Anisotropic Bianchi type VI0 Space-Time with Barotropic Fluid in Sáez - Ballester Theory of Gravitation - Kumawat, P.; Goyal, R.; Choudhary, S. (Journal of Scientific Research, 2024)
In this paper, we have discussed the exact solution of Einstein's field equations for anisotropic Bianchi type VI0 cosmological model in the framework of the scalar-tensor theory of gravitation given by Sáez–Ballester for barotropic fluid distribution. To obtain an exact solution, we have assumed that expansion (θ) is proportional to shear (σ) which leads to A =Bk, where k is a constant A and B are metric potentials and also assumed barotropic condition p = γρ; (0 ≤ γ ≤ 1) where p being isotropic pressure and ρ is matter density. Some physical and geometrical properties of the model are also discussed.